Contra eletrodos de sulfetos metálicos aplicados a células solares sensibilizadas por pontos quânticos - Soares, Leandro Luiz (2019)
The quantum dot-sensitized solar cells (CSSPQ) are considered as third generation solar cell, derived from dye-sensitized solar cells (CSSC). Several works in the literature shown that the optimization of counter electrodes (CE) is an important factor to improve the CSSPQs performance. In this study different types of CE and its production methods were evaluated by electrochemical techniques as cyclic voltammetry and electrochemical impedance spectroscopy, as well as physic techniques as X-Ray Diffraction (DRX) and scanning electron microscope (SEM). Initially, it prepared NbS2 films by spray pyrolysis at 500 and 700 ºC deposited over brass. The film treated at 700 ºC presented higher crystallinity and current density in cyclic voltammetry and smaller resistance to the charge transfer. However, the brass substrate presented problems of leaking in the moment of the device confection and, this film could not be applied in the cell. In order to avoid the leak, the brass was substituted by glass covered by fluorine-doped tin oxide (FTO) and the NbS2 films were supported by carbon-black and deposited by drop. Electrochemical characterization showed that this material presented a resistance of charge transfer of 164,24 Ω that is smallest than the FTO/Pt resistance that was 3,29 kΩ and also a higher current density. Even thought, carbon-black interfered in the surlyn® adherence, which made harder to seal effectively the device, occasioning that way a leaking in the supporting electrolyte, making also impossible to apply this material in the solar cell. The materials CuS and CuGaS2 electrodeposited potentiostatically over FTO were also tested. Both of them present better electrochemistry properties than FTO/Pt CE. The electrode CuGaS2 presented a higher density value than the CuS and Pt. The resistance value of charge transfer was close for both materials, but the CuGaS2 electrode presented a higher current density for the polysulfides redox process. After the individual CEs characterization, four different devices were constructed with the structure photoelectrode/TiO2/PQ/polysulfides electrolyte/CE. The photovoltaic device study shown that the PbS quantic point with CdS chemical bath increase 10 times the current density if the short circuit (Jsc), when compared to the device just with PbS. The device with CuGaS2 CE conducted to a improve in the fill factor (FF) doubling the solar cell efficiency if compared to the device with the same photoanode but with the FTO/Pt CE.